PHOTODYNAMIC THERAPY AND SPECIFIC ANTITUMOR IMMUNE THERAPY IN THE STRUCTURE OF INTEGRATED TREATMENT OF PATIENTS WITH MALIGNANT ASTROCYTIC SUPRATENTORIAL TUMORS. LONG-TERM TREATMENT RESULTS - V. E. Olyushin; D. M. Rostovtsev; G. V. Papayan; M. V. Filatov; T. N. Fadeyeva (Медицинский вестник Юга России, 2014)
Purpose: to determine effectiveness of new technologies together with the methods included in the standards of treatment of malignant astrocytic tumors, by evaluating long-term results of integrated treatment of patients with malignant astrocityc tumors.Materials and methods: we have evaluated long-term results of treatment of 356 patients with malignant astrocytic supratentorial tumors (anaplastic astrocytomas, glioblastomas, giant cell glioblastomas, gliosarcomas). In addition to standard treatment (surgery, chemo- and radiotherapy) 37 patients had photodynamic therapy, 82 – specific antitumor immune therapy, 19 – both therapies. In 201 patients the structure of integrated treatment included only standard methods. A separate group was composed of 17 patients who had only stereotaxic biopsy as a stage of surgical treatment. Data obtained 6 months and later after surgery are referred to as long-term results.Results: photodynamic and specific antitumor immune therapy in patients with  malignant supratentorial astrocytic tumors was safe and did not result in any adverse events increasing in comparison with control group. Better results were achieved in the group of patients who had photodynamic therapy. Photodynamic therapy application revealed to increase medium life expectancy (up to 50.79 and 47.86 months in patients with anapestic astrocitomas and glioblasomas respectively), and median survival (up to 35 months in patients with anaplastic astrocitomas and up to 30 months in patients with glioblastomas), as well as it decreases the risk of tumor recurrence. The use of photodynamic therapy together with specific antitumor immune therapy in addition to standard treatment methods did not reveal any significant advantages in comparison with photodynamic or standard treatment methods application only. Specific antitumor immune therapy based on autologous dendritic cells, also increases both medium life expectancy (anaplastic astrocytomas – 50.21 mths., glioblastomas – 23.72 mths.) and median survival (32 and 24 months respectively), when 3 courses and more are administered. 1 or 2 courses of immune therapy have no significant impact on medium life expectancy or median survival.Summary: development and clinical practice application of photodynamic therapy and specific antitumor immune therapy based on autologous dendritic cells is a perspective trend for future investigation and study, which will allow to improve long-term results of treatment of patients.